Genetic turnovers and northern survival during the last glacial maximum in European brown bears. Issue 10 (16th April 2019) - Ersmark, Erik; Baryshnikov, Gennady; Higham, Thomas; Argant, Alain; Castaños, Pedro; Döppes, Doris; Gasparik, Mihaly; Germonpré, Mietje; Lidén, Kerstin; Lipecki, Grzegorz; Marciszak, Adrian; Miller, Rebecca; et al.
Abstract: The current phylogeographic pattern of European brown bears ( Ursus arctos ) has commonly been explained by postglacial recolonization out of geographically distinct refugia in southern Europe, a pattern well in accordance with the expansion/contraction model. Studies of ancient DNA from brown bear remains have questioned this pattern, but have failed to explain the glacial distribution of mitochondrial brown bear clades and their subsequent expansion across the European continent. We here present 136 new mitochondrial sequences generated from 346 remains from Europe, ranging in age between the Late Pleistocene and historical times. The genetic data show a high Late Pleistocene diversity across the continent and challenge the strict confinement of bears to traditional southern refugia during the last glacial maximum (LGM). The mitochondrial data further suggest a genetic turnover just before this time, as well as a steep demographic decline starting in the mid‐Holocene. Levels of stable nitrogen isotopes from the remains confirm a previously proposed shift toward increasing herbivory around the LGM in Europe. Overall, these results suggest that in addition to climate, anthropogenic impact and inter‐specific competition may have had more important effects on the brown bear's ecology, demography, and genetic structure than previously thought. Abstract : The European brown bear has been routinely used to exemplify the expansion and contraction of species during glaciations. Our results indicate a major genetic and dietary shift just before the last glacial maximum, as well as the presence of bears in mid‐latitude Europe during the peak of this cold period.